Assessment of Participation within the International Classification of Functioning, Disability, and Health (ICF): The Turkish Validity and Reliability of the Participation Scale - Onur Altuntaş; Esma Özkan; Barkın Köse; Orkun Tahir Aran; Meral Huri; Esra Akı (Occupational Therapy International)
Objective. The aim of the study was to investigate the reliability and validity of the Turkish version of the Participation Scale (P-Scale). Methods. A total of 152 students, with a mean age of 20.27±2.19, participated in the study. Sociodemographic information (age, gender, and family income) was recorded; all participants completed the P-Scale twice with a 15-day interval. Translation and cross-cultural adaptation were performed to analyze the validity and reliability of the P-Scale. Cronbach’s alpha and McDonald’s alpha were used for scale reliability statistics and explanatory (EFA) and confirmatory (CFA) factor analysis; Mardia’s multivariate normality and assumption tests were used for the validity of the scale. The factor extraction methods were minimum rank factor analysis in EFA and weighted least squares mean and variance adjusted estimator polychoric correlation matrix in CFA. Results. Internal consistency of the scale was found good with Cronbach’s alpha (0.852) and excellent with McDonald’s alpha (0.924). The EFA and CFA resulted in two-factored structure, with the explained variance found to be higher than 30%. Conclusions. Analysis demonstrated that the P-Scale had a satisfactory level of reliability and validity in Turkish university students.